Pengembangan Media Smart Book Berbasis Inkuiri Terbimbing untuk Meningkatkan Hasil Belajar IPAS - Devi Riana Putri; Desi Wulandari (Postgraduate, University of Mataram, 2025)
The lack of use of learning media and the use of learning models that do not involve students are problems in learning IPAS. This study aims to develop and test the feasibility and effectiveness of guided inquiry-based smart book media to improve IPAS learning outcomes in grade IV material on changing energy forms. Data collection techniques using test techniques in the form of pretest posttest. Non-test techniques in the form of interviews, observations, documentation, and questionnaires. The results showed that the guided inquiry-based smart book media met the eligibility criteria with a score of 96.25% from media experts and 91.60% from material experts with very feasible criteria. The effectiveness of the media is seen from the increase in learning outcomes by 30.23 with an N-gain value of 0.62 with moderate criteria and t test with a sig. (2-tailed) value of 0.000 <0.005 which shows a significant difference before and after the use of learning media. Based on these results, it can be concluded that the guided inquiry-based smart book media is feasible and effective for improving the learning outcomes of IPAS fourth grade students of SDN Turusgede on the material of changing the form of energy.